MATLAB/SIMULINK BASED ANALYSIS OF VOLTAGE SOURCE INVERTER WITH SPACE VECTOR MODULATION - Auzani Jidin; Tole Sutikno (Universitas Ahmad Dahlan, 2009)
Space vector modulation (SVM) is the best modulation technique to drive 3-phase load such as 3-phase induction motor. In this paper, the pulse width modulation strategy with SVM is analyzed in detail. The modulation strategy uses switching time calculator to calculate the timing of voltage vector applied to the three-phase balanced-load. The principle of the space vector modulation strategy is performed using Matlab/Simulink. The simulation result indicates that this algorithm is flexible and suitable to use for advance vector control. The strategy of the switching minimizes the distortion of load current as well as loss due to minimize number of commutations in the inverter.